Do the Reclaimed Fungal Communities Succeed Toward the Original Structure in Eco-Fragile Regions of Coal Mining Disturbances? A Case Study in North China Loess—Aeolian Sand Area - Ji, Chuning; Huang, Jiu; Yu, Haochen; Tian, Yu; Rao, Xunzheng; Zhang, Xin (Frontiers in Microbiology, 2022)
Mining activity has caused serious environmental damage, particularly for soil ecosystems. How the soil fungal community evolves in mine reclamation and what are the succession patterns of molecular ecological networks still needs to be studied in depth. We used high-throughput sequencing to explore the changes of soil fungal communities, molecular ecological networks, and interactions with soil environmental factors in five different ages (the including control group) during 14 years of reclamation in eco-fragile mines. The results showed that the abundance and diversity of soil fungi after 14 years of reclamation were close to, but still lower than, those in the undisturbed control area, but the dominant phylum was Ascomycota. Soil nitrate-N, C/N ratio, pH, and water content significantly affected the fungal community with increasing reclamation ages. Moreover, we found that Mortierellomycota, despite its high relative abundance, had little significant connectivity with other species in the molecular ecological network. Fungal molecular ecological networks evolve with increasing ages of reclamation, with larger modules, more positive connections, and tighter networks, forming large modules of more than 60 nodes by 9 ages. The large modules were composed mainly of Ascomycota and Basidiomycota, which can form mycorrhiza with plant roots, and are not only capable of degrading pollution but are also "encouraged" by most (more than 64%) physicochemical factors in the soil environment. The results can provide a basis for scientific mine ecological restoration, especially for eco-fragile regions.